2021
DOI: 10.3390/foods10030675
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Tyrosinase Inhibitor Peptides with Copper Chelating, UV-Absorption and Antioxidant Activities: Kinetic and Docking Studies

Abstract: Nature-derived tyrosinase inhibitors are of great industrial interest. Three monophenolase inhibitor peptides (MIPs) and three diphenolase inhibitor peptides (DIPs) from a previous study were investigated for their in vitro tyrosinase inhibitory effects, mode of inhibition, copper-chelating activity, sun protection factor (SPF) and antioxidant activities. DIP1 was found to be the most potent tyrosinase inhibitor (IC50 = 3.04 ± 0.39 mM), which could be due to the binding interactions between its aromatic amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Therefore, procyanidins, caffeoylquinic acids, and phenolic glycosides contribute significantly to the antioxidant capacity and TYR inhibition activity of P. fortuneana fruits. Furthermore, tryptophan also has a strong contribution, which is consistent with studies that tryptophan has a good antioxidant capacity and can form complexes with TYR, thereby inhibiting its activity (Baenas et al., 2023; Yap & Gan, 2021). Therefore, the seven screened components significantly influence the classification of P. fortuneana fruits at different developmental stages.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, procyanidins, caffeoylquinic acids, and phenolic glycosides contribute significantly to the antioxidant capacity and TYR inhibition activity of P. fortuneana fruits. Furthermore, tryptophan also has a strong contribution, which is consistent with studies that tryptophan has a good antioxidant capacity and can form complexes with TYR, thereby inhibiting its activity (Baenas et al., 2023; Yap & Gan, 2021). Therefore, the seven screened components significantly influence the classification of P. fortuneana fruits at different developmental stages.…”
Section: Resultssupporting
confidence: 84%
“…It has been reported that tyrosinase inhibitory peptides should be composed with arginine and/or phenylalanine for strong binding with tyrosinase and inhibitory activity. Additionally, hydrophobic amino acids such as valine, alanine, and leucine, as well as aromatic residual of threonine and tyrosine, are also essential for the activity of tyrosinase inhibitory peptides [ 37 , 38 ]. The anti-melanogenic potential of sericin was discovered through its activity as a mushroom tyrosinase inhibitor [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For peptides, diphenolase inhibitory peptides interact with aromatic amino acid residues and chelate copper ions within the active site adjacent to the substrate-binding pocket. The GYSLGNWVCAAK peptide acts as a competitive inhibitor with copper chelating activity [133]. Recently, from rice-bran albumin, the SSEYYGGEGSSSEQGYYGEG peptide has been shown to have effective tyrosinase inhibitory and copper-chelating activities.…”
Section: Copper Chelating Tyrosinase Inhibitorsmentioning
confidence: 99%